2023
DOI: 10.3390/pr11071925
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Organic Powders on Surface Quality in Abrasive Blasting Process

Abstract: Abrasive blasting, sometimes known as sandblasting, is a method used to change the surface condition of materials, clean surfaces, and prepare surfaces for applications such as paint, bonding, coating, etc. The abrasive materials used in abrasive blasting are applied to the surface with compressed air or water and vary according to the purpose of application. The abrasive materials used have negative effects on the environment and human health. So far, organic materials have been used in limited applications i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…In a study on the influence of organic powder on surface quality in the abrasive blasting process, the use of three different organic wastes (walnut shells, olive pomace, and seashells) obtained through recycling in abrasive blasting was investigated. It was found that the blasting distance and time had the most significant impact on surface roughness [6].…”
Section: Introductionmentioning
confidence: 99%
“…In a study on the influence of organic powder on surface quality in the abrasive blasting process, the use of three different organic wastes (walnut shells, olive pomace, and seashells) obtained through recycling in abrasive blasting was investigated. It was found that the blasting distance and time had the most significant impact on surface roughness [6].…”
Section: Introductionmentioning
confidence: 99%